The Critical Success Factors of Enterprise Resource Planning (ERP) Implementation: Malaysian and American Experiences - Adam, Mohd Nazri Khan (2009)
This study reports the Enterprise Resource Planning (ERP) experiences of Malaysian and the USA companies. The aim of the research is to examine the critical success factors needed to ensure success of ERP implementation and to explore the impact of ERP on various operational performance measures.